Counter-Ideology as a Wider Strategy for Defeating the Boko Haram Terrorist Group - Ayima, Kwesi (2019)
There is a need to address current military strategies to defeat the resilience of the Boko Haram Terrorist (BHT) group. The purpose of this qualitative study was to provide a counter-ideology framework as an alternative strategy to defeat the group. The relational/vengeance and relative deprivation theories provided the theoretical foundation for the study, and the research question addressed the extent to which counter-ideology strategies can be instituted to defeat the BHT group. Data were collected through semi structured interviews from 20 participants who were Muslim clerics, community leaders, and military personnel, and data were analyzed using Nvivo software. The themes for the study were developed using a content analysis approach. The findings indicated that the resilience of Boko Haram was due to the group's ability to maintain an ideological consistency with the extreme version of Jihadi-Salaﬁsm. Thus, there is a need to develop an effective reconciliatory national security strategy that is focused on counter-ideology policies to augment the ongoing military strategy. Given that counter-ideology offers a nonmilitary counterterrorism approach, it can deescalate the security situation in Northeast Nigeria, which can lead to socioeconomic benefits for the youth in Nigeria